2022
DOI: 10.1038/s41598-021-04622-9
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of anosmia in hamsters infected with SARS-CoV-2 is correlated with repair of the olfactory epithelium

Abstract: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is responsible for a pandemic affecting billions of people worldwide. Apart from the extreme global economic impact, the pandemic will likely have a lasting impact through long-term sequelae not yet fully understood. Fully understanding the mechanisms driving the various symptoms and sequelae of SARS-CoV-2 infection will allow for the eventual development of therapeutics to prevent or treat such life-altering symptoms. In this study, we developed a b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 22 publications
3
40
0
Order By: Relevance
“…Alternatively, SARS-CoV-2 infection of olfactory bulbs may result in loss of a physical barrier, enabling the introduction of microbiome commensals which could contribute to the inflammatory profile. This latter hypothesis is supported by recent evidence that SARS-CoV-2 can induce gross morphological changes in the olfactory epithelium characterized by thinning and sloughing of the tissue that would normally prevent bacterial commensals from interacting with the OB ( 96 ). The extent to which the olfaction system contributes to the persistent inflammatory processes described within our study remains to be determined.…”
Section: Discussionmentioning
confidence: 66%
“…Alternatively, SARS-CoV-2 infection of olfactory bulbs may result in loss of a physical barrier, enabling the introduction of microbiome commensals which could contribute to the inflammatory profile. This latter hypothesis is supported by recent evidence that SARS-CoV-2 can induce gross morphological changes in the olfactory epithelium characterized by thinning and sloughing of the tissue that would normally prevent bacterial commensals from interacting with the OB ( 96 ). The extent to which the olfaction system contributes to the persistent inflammatory processes described within our study remains to be determined.…”
Section: Discussionmentioning
confidence: 66%
“…SARS-CoV-2 primarily targets the sustentacular cells in the olfactory mucosa, leading to a transient, massive necrosis and disintegration of the epithelium 21 . This phenomenon in hamsters is associated with the development of anosmia, a frequent clinical feature of COVID-19 patients [21][22][23] . In addition, it is also reported in some patients and in hamsters that the development of prolonged loss of smell could be caused by virus persistence in the olfactory mucosa 24 .…”
Section: Discussionmentioning
confidence: 96%
“…Olfactory and taste dysfunctions are common in mildly symptomatic COVID-19 patients. The food-searching behavioral test showed that anosmia may happen in SARS-CoV-2-infected hamsters, and the level of anosmia was associated with olfactory epithelium damage (Reyna et al, 2022). In addition, high titers of SARS-CoV-2 were found in the hamster lungs and intestines.…”
Section: Rodent Models Of Covid-19mentioning
confidence: 98%